2011
DOI: 10.1111/j.1365-2923.2010.03911.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical students learning intimate examinations without valid consent: a multicentre study

Abstract: Despite clear policies at each school, students in all schools observed or performed intimate examinations or procedures without having gained valid consent from the patient. Faculty development initiatives are clearly essential to help clinical teachers put intimate examination policy into practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 19 publications
2
59
0
2
Order By: Relevance
“…The second finding suggests that students' empathy for patients related to unjustified unethical events does not decline across their education, but remains steady [2]. Indeed, across many of our studies investigating students' dilemmas, students frequently reported experiencing distress during and sometimes up to a year after these events and narrated events with a great deal of negative emotion [2,[6][7][8]11]. Having examined students' emotional reactions to their experiences of professionalism dilemmas, we now consider in greater depth students' actions in the face of their dilemmas and the reasons they give for such actions.…”
Section: Moral Distress and Its Correlatesmentioning
confidence: 99%
See 4 more Smart Citations
“…The second finding suggests that students' empathy for patients related to unjustified unethical events does not decline across their education, but remains steady [2]. Indeed, across many of our studies investigating students' dilemmas, students frequently reported experiencing distress during and sometimes up to a year after these events and narrated events with a great deal of negative emotion [2,[6][7][8]11]. Having examined students' emotional reactions to their experiences of professionalism dilemmas, we now consider in greater depth students' actions in the face of their dilemmas and the reasons they give for such actions.…”
Section: Moral Distress and Its Correlatesmentioning
confidence: 99%
“…Rees and Monrouxe also examined 71 narratives of medical students who were asked by senior clinicians to undertake intimate examinations without valid patient consent to understand students' reasoning concerning why they complied or resisted and, if they resisted, how [11]. Only 18 percent reported resisting senior clinicians' requests to conduct intimate examinations without valid patient consent.…”
Section: Professionalism Dilemmas: Acts Of Resistance and Compliancementioning
confidence: 99%
See 3 more Smart Citations